Determination of prevalence and risk factors for infection with Babesia ovis in small ruminants from Turkey by polymerase chain reaction - Aktas, Munir; Altay, Kursat; Dumanli, Nazir (Springer, 2007)
In this study, PCR and thin blood smear-based diagnostic methods were used to assess the frequency of Babesia infection in small ruminants. A total of 300 sheep and 100 goats from 37 randomly selected herds located in eight locations of eastern Turkey were examined for the presence of Babesia infection and any tick species on the body of the animals. Of 400 blood samples examined, 6 (1.5%) were positive for Babesia spp. piroplasms upon microscopic examination, whereas 33 (8.25%) were positive for the presence of B. ovis by PCR. The prevalence of babesiosis in small ruminants detected by PCR was significantly higher than obtained in microscopic examination of thin blood smears ( P < 0.05). Thirty-three animals produced the DNA fragment specific for Babesia ovis of which 32 ( 10.66%) were sheep and 1 (1%) was goat. The difference between the prevalence of Babesia infection in sheep and goats were statistically significant ( P < 0.05). The prevalence of Babesia infection in different age groups of sheep were statistically non-significant (P > 0.05). The frequency of B. ovis infection was higher in herds with tick burden than no tick burden ( P < 0.05). Seven amplicons ( six from sheep and one from goat) were sequenced. The resulting sequences were identical to the recently reported nucleotide sequence of B. ovis. A total of 510 ticks belonging to the Rhipicephalus spp. were collected from sheep. Ticks were identified to be R. bursa and R. turanicus on the basis of morphological features.
Keywords: Mashhad Suburb; Sheep; Theileria; Bovis; Piroplasms; Diagnosis; Khorasan; Province